Effect of seed size and phosphorus fertilization on growth of selected legumes - Kolawole, G.O.; Kang, B.T. (Informa UK Limited, 1997)
A screenhouse experiment was conducted to assess the effects of seed size and phosphorus (P) fertilization on growth of 12 herbaceous and shrub legumes [Arachis hypogaea, Cajanus cajan, Centrosema pascuorum, Centrosema brasilianum, Crotolaria ochroleuca, Glycine max, Lablab purpureus, Mucuna cochinchinensis, Mucuna pruriens var. utilis (black seed), Mucunapruriens (white seed), Pueraria phaseoloidesand Vigna unguiculata] grown on a P‐deficient Plinthustalf. Species with large seed size showed higher biomass accumulation, nodulation and higher plant nutrient element content. However, response to P fertilization was higher in small size seeded species. Plant top dry weight was highly correlated with seed weight and seed nutrient element contents. Although P application significantly increased nitrogen (N), P, potassium (K), calcium (Ca), and magnesium (Mg) contents of plant tops, high rate of P fertilization appeared not to be beneficial to the early growth of the species tested on this P‐deficient soil. The use of large seed size with high seed nutrient element contents is highly recommended for fast establish ment of fallow legume species intended for use in production systems on P‐deficient soils.